Self-Rolling Yoga Mat / Adam Roslan ... [et al.] - Roslan, Adam; Mohamad Sani, Mohamad Hariz; Muhamad Herry Chan, Muhammad Amirul; Mohd Nizam, Muhammad Hazwan; Mazelan, Najwa Syafiqah; Mohd Yusni, Nor Husnina; Mohd Noh, Shuhaidah (2022)
Nowadays, yoga mats are vital equipment that many people use during workouts or exercise. Yoga mats are easy to get at any big store or sports store. This equipment provides a surface for the users to perform any exercise comfortably. Due to technological advancement, yoga mats can be improvised to a better version and use innovative ideas to make the product have more functions for the consumer. SELO Mat is a yoga mat created by us with improvements and the implication of a "slap bracelet" technology. This technology allows SELO Mat to roll on its own after use. We target this product to students, travellers and athletes. SELO Mat is priced at RM89.90 for small size, RM129.90 for medium size and RM179.90 for large size. Before we open the price of the research and development, we have made a study related to the price that will be placed; the purpose of this is to provide satisfaction with the quality of goods and reasonable prices to our potential consumers. We believe that our products can provide satisfaction in terms of materials used and existing technology. Our profit is 50% of the cost price for potential investors, which is RM30.70 for small size, RM44.80 for medium size, and RM61.30. The project is led by Muhammad Amirul Muhamad Herry Chan as General Manager and assisted by his team, namely Muhammad Hazwan Bin Mohd Nizam as Assistant Manager, Mohamad Hariz Bin Mohamad Sani as Administrative Manager, Nor Husnina Binti Mohd Yusni as Financial Manager, Adam Bin Roslan as Operating Manager, Najwa Syafiqah Binti Mazelan as Research & Development Manager and Shuhaidah Binti Mohd Noh as Marketing Manager.